The long non‐coding RNA SPRY4‐IT1: An emerging player in tumorigenesis and osteosarcoma - Li, Zheng (Cell Prolif, 2018)
Accumulating evidence from genome‐wide analysis and functional studies has begun to unveil the important role of long non‐coding RNAs (lncRNAs) in cancer development. The lncRNA SPRY4‐IT1 is derived from an intron of SPRY4 gene and was originally reported to be upregulated in melanoma in which it functioned as an oncogene. Since this discovery, an increasing number of studies have investigated the expression and function of SPRY4‐IT1 in human cancers. Aberrant expression of SPRY4‐IT1 has now been documented in different cancer types, including osteosarcoma, breast, renal, oesophageal and prostate cancers. However, its deregulation and function in lung and gastric cancers remain controversial. Pertinent to clinical practice, SPRY4‐IT1 expression has been shown to predict survival of cancer patients. In this review, we summarize recent evidence concerning SPRY4‐IT1 deregulation and the associated mechanisms in human cancers. We also discuss the potential clinical utilization of this lncRNA as a diagnostic and prognostic biomarker for cancer patients.